Auditing - Millichamp, A.H. (Alan H.) (Continuum, 2001)
This edition includes relevant statements of auditing standards and practice notes. It can be used on the following courses - ACCA, AAT, BTEC, HNC/D in business, finance, and computer studies, BA in accounting and CIPFA